ANALISIS KINERJA DAN TINGKAT PELAYANAN FASILITAS PEJALAN KAKI DI KAWASAN STASIUN KARET - Firman Prayogi; Sigit Priyanto; Imam Muthohar (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2020)
Karet Station has an average number of passengers at 12,594 people per day in 2018, has a large potential of pedestrian trip generation. The basic problem experienced by pedestrians at Karet Station is when they (KRL passengers) leave the station, they cannot find a clear pedestrian path to accommodate their movement towards other public transport facilities. As the result, the pedestrians scattered and even crossed the road and stopped the public transportation arbitrarily. This activity causes a high risk of accidents and traffic flow constraints caused by reduced capacity of road section due to public transport activities while waiting, lowering, and raising passengers. The purpose of this research was to analyze the pedestrian lane characteristics, and service level based on technical guidelines and stated preferences of passangers. In this research, the primary data were collected by conducting direct surveys in study area to get characteristics of pedestrian, traffic flow, and passanger perception about pedestrian facilities performance. Analytical results from this study conclude that from technical guidelines approach, there are two sidewalk segments in the Karet Station area which require special attention with the level of service categori at C and E level, and also requires improved pedestrian crossing facilities from zebra cross type to be underpass or pedestrian bridge. Based on stated preferences approach, from the assessment of 24 service attributes, there are 6 attributes of lowest performance services included in quadrant I of Importance Performance Analysis (IPA) matrix which are the main priority that must be resolved immediately.